RUNX1 Mutations Are Associated With Poor Outcome in Younger and Older Patients With Cytogenetically Normal Acute Myeloid Leukemia and With Distinct Gene and MicroRNA Expression Signatures - Mendler, Jason H. (American Society of Clinical Oncology, 2012)
PURPOSE: To determine the association of RUNX1 mutations with therapeutic outcome in younger and older patients with primary cytogenetically normal acute myeloid leukemia (CN-AML) and with gene/microRNA expression signatures. PATIENTS AND METHODS: Younger (< 60 years; n = 175) and older (≥ 60 years; n = 225) patients with CN-AML treated with intensive cytarabine/anthracycline-based first-line therapy on Cancer and Leukemia Group B protocols were centrally analyzed for RUNX1 mutations by polymerase chain reaction and direct sequencing and for established prognostic gene mutations. Gene/microRNA expression profiles were derived using microarrays. RESULTS: RUNX1 mutations were found in 8% and 16% of younger and older patients, respectively (P = .02). They were associated with ASXL1 mutations (P < .001) and inversely associated with NPM1 (P < .001) and CEBPA (P = .06) mutations. RUNX1-mutated patients had lower complete remission rates (P = .005 in younger; P = .006 in older) and shorter disease-free survival (P = .058 in younger; P < .001 in older), overall survival (P = .003 in younger; P < .001 in older), and event-free survival (P < .001 for younger and older) than RUNX1 wild-type patients. Because RUNX1 mutations were more common in older patients and almost never coexisted with NPM1 mutations, RUNX1 mutation–associated expression signatures were derived in older, NPM1 wild-type patients and featured upregulation of genes normally expressed in primitive hematopoietic cells and B-cell progenitors, including DNTT, BAALC, BLNK, CD109, RBPMS, and FLT3, and downregulation of promoters of myelopoiesis, including CEBPA and miR-223. CONCLUSION: RUNX1 mutations are twice as common in older than younger patients with CN-AML and negatively impact outcome in both age groups. RUNX1-mutated blasts have molecular features of primitive hematopoietic and lymphoid progenitors, potentially leading to novel therapeutic approaches.